Facilitated ammonia decomposition and enhanced hydrogen diffusion in 10Ni-Ce0.8Zr0.2O2 as anode catalytic functional layer for low-temperature direct ammonia fuel cells - Jia, Weihua (2025)
Due to higher volumetric energy density and more efficient transportation of ammonia in contrast to hydrogen, ammonia has propelled DAFCs into the spotlight of research and development in recent years. To enhance their performance, a novel design strategy is employed by introducing the catalytic functional layer onto the surface of anode in single cells to substitute traditional anode material modification approaches. In this study, xNi-Ce0.8Zr0.2O2 (xNi-CZ, x = 5 wt%, 10 wt%, 15 wt%) catalysts are synthesized and their phase structures are analyzed. The physiochemical properties including, microstructure, reduction capability, ammonia adsorption capacity, elemental valence states and ammonia decomposition conversions for as-prepared catalysts are characterized and evaluated by SEM&TEM, H2-TPR, NH3-TPD, XPS, fixed-bed reactor, respectively. Based on the TEM images, a theoretical calculation model is developed by utilizing DFT, and the reaction pathways and rate-determining steps for ammonia decomposition are analyzed and determined. Moreover, the 10Ni-CZ|Ni-YSZ|YSZ|GDC|LSCF-GDC structure is constructed by employing 10Ni-CZ as a catalytic functional layer, and the impedances and power outputs are tested at 550–650 °C. Experimental results indicate that the incorporation of 10Ni-CZ in LT-DAFCs can notably reduce the impedance by 24.46 % and significantly increase the maximum power density by 11.04 % at 650 °C as expected, demonstrating that adding 10Ni-CZ could be a highly effective and practical strategy for advancing LT-DAFCs technology.